Confederate Daughters : Coming of Age during the Civil War - Ott, Victoria E., 1971- (Book collections on Project MUSE., 2008)
Confederate Daughters: Coming of Age during the Civil War explores gender, age, and Confederate identity by examining the lives of teenage daughters of Southern slaveholding, secessionist families. These young women clung tenaciously to the gender ideals that upheld marriage and motherhood as the fulfillment of female duty and to the racial order of the slaveholding South, an institution that defined their status and afforded them material privileges. Author Victoria E. Ott discusses how the loyalty of young Southern women to the fledgling nation, born out of a conserv.